The Influence of Short Pulse Er:Cr: YSGG Laser on the Shear Bond Strength of Cad-Cam Zerconia Material to Resin Cement - Fateima Sameir Muhammed; Hussein Ali Jawad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Surface enhancement of CAD-CAM zerconia for increasing the matching to resin cement, using Er:Cr:YSGG Laser.Materials and Methods: 40 sintered zerconia disc specimens( VITAYZ HT) were prepared. They are dividedinto six groups, each group of seven samples.Laser groups are depending on laser power, laser irradiation time and pulse duration, group(A): 20 s, 60µs pulse duration. Group (B): 30 s , 60 µs pulse duration. Group (C): 40 s, 60 µs pulse duration. Group (D): 20 s, 700 µs pulse duration. And group (E): 30 s, 700 µs pulse duration, for different powers (1, 1.50, 2, 2.50, 3, 3.50, 4) W.Luting cementwas bonded to treated zerconia surfaces and light cured for 40 s.The Shear bond strength was measured using a universal testing machine. The optained results were stastistically analyzed. Thebond failur modes were also examined.Results: There was a clear increment in the shear bond strength especielly in group B (4 W, 30 s,60 µs) reaching to 8.63 Mpa.No crackes were observed.Conclusion: It was detected that the shear bond strength was related to the pulse depth.The pulse duration of Er:Cr:YSGG is a crucial parameter in the enhancement of zirconia ceramic surface.